1992
DOI: 10.1111/j.1600-0536.1992.tb05211.x
|View full text |Cite
|
Sign up to set email alerts
|

Shiitake (Lentinus edodes) dermatitis

Abstract: Shiitake (Lentinus edodes) is a mushroom which is eaten in Chinese: and Japanese meals and is nowadays the second most commonly produced edible mushroom in the world Shiitake was first described by Nakamura in 1977. This disease presents with very characteristic skin nabufestations. From April 1974 to April 1991, I have observed 51 patients with shiitake dermatitis the following description reviews the clinical manifestations, laboratory investigations and sources of shiitake dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
138
0
11

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(151 citation statements)
references
References 2 publications
2
138
0
11
Order By: Relevance
“…It is a flagellate dermatitis that is seen about 2 days after consumption of raw or incompletely cooked shiitake mushrooms in susceptible individuals. 1 In addition to their culinary uses, experimental studies have suggested that shiitake mushrooms could potentially confer therapeutic effects on blood pressure and cholesterol levels. 2 Lentinan, a thermosusceptible polysaccharide derived from shiitake mycelia, may also have anticarcinogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…It is a flagellate dermatitis that is seen about 2 days after consumption of raw or incompletely cooked shiitake mushrooms in susceptible individuals. 1 In addition to their culinary uses, experimental studies have suggested that shiitake mushrooms could potentially confer therapeutic effects on blood pressure and cholesterol levels. 2 Lentinan, a thermosusceptible polysaccharide derived from shiitake mycelia, may also have anticarcinogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…People who eat raw or half-cooked shiitake mushrooms (Lentinus edodes) occasionally develop ‘shiitake dermatitis’ [1, 2, 3]. This was first described by Nakamura [1].…”
Section: Introductionmentioning
confidence: 99%
“…Alle Patienten zeigten bis auf die typischen, stark juckenden Hautveränderungen keine weiteren Symptome oder pathologischen Laborwerte [6]. Das histologische Bild wird als unspezifisch beschrieben.…”
Section: Diskussionunclassified
“…Hier zeigt sich eine spongiotische Auflockerung der Epidermis, subkorneale Vesiculae, ein ödematös aufgequollenes Stratum papillare und ein dichtes interstitielles und perivaskuläres, lymphomonozytäres Infiltrat mit Eosinophilen bis in die mittlere Dermis [4]. Im Hauttest (Prick-, Scratch-, Epi-) zeigte sich in einigen Fällen eine toxische Reaktion [4], eine allergische Genese wird jedoch nicht für wahrscheinlich gehalten [6]. Aus diesem Grund verzichteten wir auch auf eine weitere allergologische Abklärung.…”
Section: Diskussionunclassified
See 1 more Smart Citation